Kehamilan dengan Covid-19 - Rijanto i Agoeng Basoek (PROCEEDING UMSURABAYA, 2023)
Abstract :Pregnant women are considered to have a high risk of morbidity and even higher mortality due to their susceptibility to viral respiratory pathogens and special immunologic conditions, during the course of pregnancy. Several studies assessed that Covid-19 infection during pregnancy was reported to cause harm. With patient manifestations with severe conditions, including spontaneous abortion, imminent preterm labor, fetal distress, preterm delivery, neonatal asphyxia, neonatal pneumonia, intra uterine fetal death (IUFD), and neonatal death. Keywords: Pregnancy, Complication, And Covid-19